Horizontal Transmission of the Entomopathogen Fungus Metarhizium anisopliae in Microcerotermes diversus Groups - Cheraghi, Amir (Insects, 2012)
An experiment was carried out in order to investigate fungal conidia transmission of Metarhizium anisopliae (Metschnikoff) Sorokin from vector (donor) to healthy Microcerotermes diversus Silvestri (Iso.: Termitidae) and determine the best donor/concentration ratio for transmission. After preliminary trials, concentrations of 3.1 × 10(4), 3.9 × 10(5), 3.2 × 10(6) and 3.5 × 10(8 )conidia mL(−1) were selected for testing. The experiment was performed at three donor : Recipient ratios of 10, 30 and 50%. The highest mortality of recipient workers was observed after 14 days at the concentration of 3.5 × 10(8) conidia mL(−1 )and donor ratio of 50%. The mortality of recipient workers was less than 20% at all concentrations at a donor ratio of 10%. Our observations indicate social behavior of M. diversus, such as grooming, can be effective in promoting epizootic outbreaks in a colony. While the current results suggest good potential for efficacy, the use of M. anisopliae as a component of integrated pest management of M. diversus still needs to be proven under field conditions.